Messiness in international qualitative interviewing: What I did, what I didn’t do, and a little bit about why - Field, Rebecca; Barns, Angela; Chung, Donna; Fleay, Caroline (2021)
This is a reflexive account of the messiness experienced by a Persian-Australian doctoral researcher interviewing social work and human service practitioners and people seeking asylum in Germany. This data collection was part of a cross-national comparative study of the impacts of policy on the experiences and perceptions of people seeking asylum and social work and human service practitioners in Bavaria and Western Australia. Through interview stories and the work of others, this article offers a first person account of the complexities, ambiguities and dilemmas that can occur before, during and after data collection, how these were navigated through the use of Finlay's (2012) five lenses for the reflexive interviewer, and some of the lessons learnt.